Meditations on Ortega y Gasset's Opaque Dogs: Hunting with Dogs as Inter-Species Affective Scaffolding. - du Toit, Jean; Swer, Gregory Morgan (Topoi: An International Review of Philosophy, 2025)
This paper interprets Ortega y Gasset's Meditations on Hunting (1972) through the concept of cognitive scaffolding in order to analyse the relationship between hunter and hunting dog as a form of inter-species distributed cognitive system. In recreational hunting, the hunter and the dog engage in a reciprocal process of mutual cognitive scaffolding that transforms both their capacities. It is further argued that this scaffolding also serves as a means of affective regulation, and that it is the affective rather than the cognitive features of the system that point to the function of the scaffolding. Namely, the production of an affective state in the hunter. We detail the ways in which the cognitive and affective features of the scaffold operate and interrelate. We then explore the role of the game-animal in the affective functioning of the scaffold and consider that the hunter-dog system might represent a harmful form of scaffolding.